Daughter of Felda Settler presented with Royal Academic Award (Excellence Award) - UMP, PNC (2018)
Seeing how dedicated her parents were to see to it that she got the best education although they themselves were not highly educated was the defining moment for Umi Zaidatul Azeera Mohd Nawi to not to take her studies lightly.